2017
DOI: 10.2147/ijn.s136748
|View full text |Cite|
|
Sign up to set email alerts
|

Antioxidant and hepatoprotective role of selenium against silver nanoparticles

Abstract: Silver nanoparticles (AgNPs) have attracted the most interest in terms of their potential biomedical and industrial applications. However, these nanoparticles have shown their toxic behavior toward environment, living tissues, and organisms. Selenium (Se), an essential trace element, is necessary for various metabolic processes, including protection against oxidative stress and immune function. The present study was undertaken to evaluate the effect of Se against AgNP-induced hepatic oxidative stress. AgNPs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 67 publications
4
30
0
Order By: Relevance
“…These results indicated that the administration of 0.5 or 1.0 mg AgNPs/kg BW did not induce the oxidative stress in rabbits under heat stress conditions. However, administration of higher doses of AgNPs (5 mg/kg/day) induced hepatic damage and oxidative stress illustrated by a significant decrease in total antioxidant capacity level and the activities of GSH-Px and superoxide dismutase in rats [35]. The decreased levels of GSH-Px due to the injection of AgNPs might be attributed to the high affinity of nanoparticles for thiol groups leading to a decrease in glutathione content due to the free radical scavenging [36].…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that the administration of 0.5 or 1.0 mg AgNPs/kg BW did not induce the oxidative stress in rabbits under heat stress conditions. However, administration of higher doses of AgNPs (5 mg/kg/day) induced hepatic damage and oxidative stress illustrated by a significant decrease in total antioxidant capacity level and the activities of GSH-Px and superoxide dismutase in rats [35]. The decreased levels of GSH-Px due to the injection of AgNPs might be attributed to the high affinity of nanoparticles for thiol groups leading to a decrease in glutathione content due to the free radical scavenging [36].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, rats co-treated with Sel demonstrably ameliorate DCF-induced hepatic injury dose-dependently, evaluated by transaminases levels in serum. 48,49 Renal function marker enzymes such as urea and creatinine are metabolic waste products primarily excreted in the urine. They are important in the diagnosis of kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…22 However, increased (p < 0.05) SOD, CAT, GST GPx activities in Sel and DCF co-treated rats showed the protective augmentation of Sel against DCF-induced oxidative stress via enhancement of antioxidant enzymes activities in line with previous findings. 48,[52][53][54] GSH acts as a cofactor of several detoxifying enzymes (e.g. GPx, GST), scavenging intracellular free radicals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These structural impairments may explain why cardiac hemodynamic parameters were affected and cardiac functions were reduced in AgNPs-exposed animals. Although there have been studies reported that selenium alleviates heavy metal and silver induced toxicity in cells and tissues, 23 , 38 40 there has been no study examining the detoxifying effect of sodium selenite on AgNPs-induced toxicity in cardiac tissue. The results from this study clearly demonstrated that treatment with selenite reduced the disarray of sarcomere and fragmentation of myofibrils, and improved capillary patency in AgNPs-exposed rats, suggesting that selenium supplementation is capable of correcting AgNPs toxicity in the heart.…”
Section: Discussionmentioning
confidence: 99%